Selected problems of applying the law in adaptation and modernization of buildings in Poland = Wybrane problemy stosowania prawa we współczesnym procesie adaptacji i modernizacji obiektów budowlanych w Polsce - Korbel, Wojciech (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Chosen problems of law implementation in the contemporary process of building`s modernization in Poland. One of the major problems in the contemporary process of building`s modernization in Poland is the pluralism of different interpretations of chosen legal terms, existing in the contemporary building code. Incorrect interpretation, results in the incorrect application to the authorities for the proper building permit and as the effect, it causes the lost of time and money. The article tries to identify some of these problems and seeks the solution to solve them, through the evolutionary method of building law creation.
Keywords: prawo budowlane; obiekty budowlane; adaptacja; modernizacja; samodzielność lokalu; zgłoszenie robót; Construction law; law interpretation; building obiects; adaptation; modernisation